Nanobody-based indirect competitive ELISA for the detection of aflatoxin M1 in dairy products - Li Yi; Haiyuan Liu; Yingda Liu; Aiyisi; Jing He; Liang Ming; Jirimutu (Scientific Reports)
Abstract Aflatoxin M1 (AFM1) is known to be carcinogenic, mutagenic, and teratogenic and poses a serious threat to food safety and human health, which makes its surveillance critical. In this study, an indirect competitive ELISA (icELISA) based on a nanobody (Nb M4) was developed for the sensitive and rapid detection of AFM1 in dairy products. In our previous work, Nb M4 was screened from a Bactrian-camel-immunized phage-displayed library. It exhibits VH-like features, possesses higher thermal stability than monoclonal antibody (mAb 1E6) and tightly binds to AFM1–BSA with a K D value of 2.5 nM. Under the optimal conditions, its half-maximal inhibitory concentration was 0.338 ng/mL, the limit of detection was 0.051 ng/mL, and linearity was noted in the range of 0.168–0.679 ng/mL. Nb M4 displayed almost no cross-reactivity with other mycotoxins. No matrix effect was observed in milk and milk powder samples, and the matrix effect in yogurt samples could be weakened by 2-fold dilution. Furthermore, validation studies in spiked samples (milk, yogurt, and milk powder) resulted in good recoveries of 95.40–111.33%, with a low coefficient of variation (2.89–6.78%). High-performance liquid chromatography was used to evaluate the accuracy and reliability of the developed icELISA, which indicated a satisfactory consistent correlation (R2 = 0.9722). This study highlights the potential of Nb M4 as a promising component for detecting AFM1 in dairy products.